1995
DOI: 10.1002/ajmg.1320600209
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive heterochromatin of chromosome 1 and Duffy blood group alleles in schizophrenia

Abstract: Cytogenetic analysis was carried out in unrelated schizophrenic patients, unrelated controls and patients and family members in multiplex families. The size distribution of chromosome 1 heterochromatic region (1qH, C-band variants) among 21 unrelated schizophrenic patients was different from that found in a group of 46 controls. The patient group had 1qH variants of smaller size than the control group (P < 0.01). Incubation of phytohemagglutinin-treated blood lymphocytes with 5-azacytidine (which causes decond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…These linkage findings justify further positional cloning studies to identify the vulnerability gene in the 1q22-31 region. Several studies had reported encouraging findings of an association of several vulnerability genes in this region with schizophrenia, such as a potassium channel gene [KCNN3], 44 a fragile site, 45 a heterochromatin variant, 46 and the Duffy blood group. 47 The chromosome region 1q41-44 covered by the markers of D1S320, D1S251, D1S404, D1S2836, and D1S180 with positive NPL scores covered a distance of 26.8 cM, especially in the broad phenotype model.…”
Section: Discussionmentioning
confidence: 99%
“…These linkage findings justify further positional cloning studies to identify the vulnerability gene in the 1q22-31 region. Several studies had reported encouraging findings of an association of several vulnerability genes in this region with schizophrenia, such as a potassium channel gene [KCNN3], 44 a fragile site, 45 a heterochromatin variant, 46 and the Duffy blood group. 47 The chromosome region 1q41-44 covered by the markers of D1S320, D1S251, D1S404, D1S2836, and D1S180 with positive NPL scores covered a distance of 26.8 cM, especially in the broad phenotype model.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently two linkage studies found significant evidence for linkage at 1q23.3, which is centromeric to the locus implicated by a cytogenetic abnormality [Brzustowicz et al, 2000;Gurling et al, 2001]. Another study combined allelic association, cytogenetic and family linkage data on chromosome 1 using heterochromatic C-band variants in the q22.1-23 region and found cosegregation of a 1qH (C-band) variant and Duffy blood group alleles with schizophrenia in a single family [Kosower et al, 1995]. Other linkage studies from Finland found significant evidence for linkage to schizophrenia in a position that was telomeric to 1q23.3 but proximal to 1q42.1 [Ekelund et al, 1997[Ekelund et al, , 2000Hovatta et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…5 The 1q21 region has been linked to familial hemiplegic migraine 16,17 but not to schizophrenia or any other neuropsychiatric disorder, 18,19 though variations in heterochromatin in the 1q21 region have been reported in schizophrenics. 20 Independent of the gene's map location, the observation of association between longer-CAG hKCa3 repeat alleles and schizophrenia was important, so we investigated hKCa3 repeat lengths in the population of the National Insitute of Mental Health (NIHM) Schizophrenia Genetics Initiative. This dataset is made up of extended families, with members both affected and unaffected with schizophrenia.…”
mentioning
confidence: 99%